Kredibilitas Sejarah dalam Konten Deepfake “Ketemu Jendral Daendels” di TikTok - Dhea Salma Rihadatul Aisyah; Vivien Febri Astuti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the historical credibility of the deepfake content titled “Ketemu Jenderal Daendels” on TikTok. The research examines users’ assessments of visual realism, attractiveness, and the historical credibility of the content as a source of historical information. This study employed a quantitative approach using a survey method. Data were collected through an online questionnaire from 97 respondents selected via purposive sampling, namely TikTok users who had watched the deepfake content. The data were analyzed using descriptive statistics and simple linear regression. The results show that the deepfake content has a high level of visual realism and attractiveness, making it effective in increasing young people’s interest in history. However, its historical credibility is rated moderate to low, particularly in terms of accuracy and trustworthiness. This study concludes that deepfake historical content on TikTok serves better as an introductory tool to spark interest in history rather than as a credible source of historical information. These findings emphasize the importance of content transparency and digital literacy in the era of artificial intelligence.